Análise da gestão de pessoas na terceirização de atividades-fim no setor financeiro cearense - Araújo, Maria Antônia do Socorro Rabelo (2005)
The present study aims to verify how outsourced (contracted) sale teams are managed by commercial banks which operate in credit on consignation competitive business in Ceara State, in order to assure a continuous, qualified and increasing business tide. First, were done teorethical approaches as “third” and “fourth” outsourcing, strategic administration, human capital management, financial market and credit on consignation negotiation. After bibliographical review, an exploratory and descriptive field research was done with commercial banks placed in Ceara which operate with lending on consignation product. Were administered four semistructured quetionnaires to banks managers, banks correspondents, internal collaborators and collectors. After, collected iformations were tabulated and received qualitative and quantitative treatment, detecting that the outsourcing of selling activities by banks are motivated by margin, funding, decentralization of sale points and by operational simplicity, as well as was identified as a disadvantage of this outsourcing process the low managing and technical capacity of its correspondent (contracted).This operational simplicity setting, as well as low managing and technical capacity, roughly contribute towards the fragility of staff employee in third and fourth outsourcing sales team management techniques by contracted companies. We believe that the lack of human resources management practices within outsourcing work endangers strategic results of action of both companies involved on this process.